Pengaruh Kompetensi Terhadap Kinerja Guru pada Masa Pandemi Covid-19 - Joko Supriyanto (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2023)
During the Covid-19 pandemic, learning at school was replaced by learning from home through distance learning by online. For this reason, teacher competence in internet technology is absolutely necessary. The purpose of this research for to get an in-depth picture and provide empirical evidence on the effect of competence on teacher performance Covid-19 pandemic and carried out in the semester II of the 2020/2021 school year at SMP Negeri 23 Hulu Sungai Tengah, Kalimantan Selatan province by using 13 teachers as a sample. The research uses quantitative methods with data collection techniques through questionnaires. The questionnaire is a closed questionnaire using a Likert scale. Data were analyzed through univariate analysis, linear regression analysis with t test and coefficient of determination (R2), and product moment correlation test from Karl Pearson, done with the help of SPSS Version 16.0 program. Based on the results and discussion, it is concluded that personality, social, pedagogical, and professional competence of teachers at SMP Negeri 23 Hulu Sungai Tengah are in line with teacher performance, especially in planning and carrying out learning, as well as carrying out assessments during the Covid-19 period. This is evidenced by the results of hypothesis testing with an rcount of 0.685 > rtable 0.553 at a significance level of 5% with an effect of 90.40% and 9.60% other influenced by other factors.